2015
DOI: 10.1371/journal.pone.0143659
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal L22-like1 (RPL22L1) Promotes Ovarian Cancer Metastasis by Inducing Epithelial-to-Mesenchymal Transition

Abstract: Double minute chromosomes (DMs) have important implications for cancer progression because oncogenes frequently amplified on them. We previously detected a functionally undefined gene amplified on DMs, Ribosomal L22-like1 (RPL22L1). The relationship between RPL22L1 and cancer progression is unknown. Here, RPL22L1 was characterized for its role in ovarian cancer (OC) metastasis and its underlying mechanism was examined. DNA copy number and mRNA expression of RPL22L1 in OC cells was analyzed using data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The fifth key gene was RPL22L1, which was identified as a trace component of ribosome ( 31 , 32 ). Wu et al reported that RPL22L1 could promote ovarian cancer metastasis by inducing epithelial-to-mesenchymal transition ( 33 ). Moreover, recent study also demonstrated that RPL22L1 could play vital and definite roles in hematopoietic development ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fifth key gene was RPL22L1, which was identified as a trace component of ribosome ( 31 , 32 ). Wu et al reported that RPL22L1 could promote ovarian cancer metastasis by inducing epithelial-to-mesenchymal transition ( 33 ). Moreover, recent study also demonstrated that RPL22L1 could play vital and definite roles in hematopoietic development ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…RPL22L1 still ranks first by p-value, after MYCN mRNA, even with all mRNAs included (p = 4.35 × 10 −74 , plot not shown). RPL22L1 has not been investigated in neuroblastoma, however it is over-expressed in metastasising and invasive ovarian tumour tissues, corresponding with the increased DNA copy number [22]. Although originally located on the 3q26.2 locus, the amplified RPL22L1 gene is co-located with amplified MYCN DNA in double minute chromosomes in the UACC-1598 ovarian cancer cell line.…”
Section: Ribosomal Proteins: Rpl22l1 Rpl39 Rpl18a Rpl36 Rpl35 Rps3mentioning
confidence: 99%
“…Double minute chromosomes are extrachromosomal cytogenetic structures and commonly found to carry oncogenes in various cancers, including epidermal growth factor receptor in gliomas, C‐MYC in CRC, and EIF5A2 or RPL22L1 in ovarian cancer. In the report presented here, we identified a novel CRC metastasis‐related gene, namely NUBPL , that was also amplified on DMs.…”
Section: Discussionmentioning
confidence: 99%